PENGARUH LATIHAN PASSING BERPASANGAN TERHADAP KETERAMPILAN PASSING KAKI BAGIAN DALAM SISWA EKSTRAKULIKULER FUTSAL SMP - Candra Candra; Dodik Mulyono; Wawan Syafutra (Jurnal Muara Pendidikan, 2022)
The effect of the inner leg paired passing practice on the passing skills of futsal extracurricular students at SMP Negeri 7 Lubuklinggau City. The experimental research method, the population of 30 people, and the sample in the study amounted to 28 exercises. The data collection technique in this research uses the futsal game passing ability test, data to be collected in this study namely pre-test and post-test. Analysis technique this test uses normality analysis and paired sample t-test. The results showed that the data processing using the SPSS 22 program stated that the data were normally distributed, hypothesis testing was found that tcount was -22,312 with a ttable value of 177, then tcount > ttable then Ha was accepted and Ho was rejected, the effect of the inner leg paired passing practice on the passing skills of futsal extracurricular students at SMP Negeri 7 Lubuklinggau City. Conclusion.